Rich versus poor : discrepancies in perceptions of ANC and NP supporters towards the poor in South Africa - Mamabolo, Nancy Matsie (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2000.